2021
DOI: 10.1161/hypertensionaha.121.16975
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microparticles in Cardiovascular Disease: Implications for Endothelial Dysfunction, Thrombosis, and Inflammation

Abstract: Microparticles are small cell vesicles that are derived from the cell membrane in response to different biological processes. There is growing evidence supporting the association between microparticles and cardiovascular disease, as their pathophysiology commonly includes endothelial damage and chronic inflammation which also promote a prothrombotic state. The direct causal link between the release of the different subtypes of microparticles and their implications on physiological and pathological conditions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 101 publications
0
34
0
Order By: Relevance
“…The differences between studies might be related to different patient cohorts included, the use of unattended AOBP, the EVs subtype (eg, platelet‐derived, endothelial‐derived) and surface markers analyzed across different studies. Alternatively, this could reflect a different underlying mechanism responsible of EVs release (eg, acute or chronic damage, vascular injury, and others) as it has been shown that the stimuli involved in their genesis has an important effect on determining the antigens that EVs express 13 . Sasone and associates showed elevated levels of EVs expressing CD62 + and CD144 + during hypertensive emergencies with a decrease in their levels after BP normalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences between studies might be related to different patient cohorts included, the use of unattended AOBP, the EVs subtype (eg, platelet‐derived, endothelial‐derived) and surface markers analyzed across different studies. Alternatively, this could reflect a different underlying mechanism responsible of EVs release (eg, acute or chronic damage, vascular injury, and others) as it has been shown that the stimuli involved in their genesis has an important effect on determining the antigens that EVs express 13 . Sasone and associates showed elevated levels of EVs expressing CD62 + and CD144 + during hypertensive emergencies with a decrease in their levels after BP normalization.…”
Section: Discussionmentioning
confidence: 99%
“…Increased circulating EVs have been related to various clinical conditions impacting on vascular integrity, endothelial function, inflammation, and thrombosis, such as hypertension, 19–22 atherosclerosis, 17,18 heart failure, 23,24 and others 25–28 . EVs can originate from different cells including platelets, and their release can be promoted by coagulation, shear stress, hypoxia and proinflammatory mediators 13,14,29,30 . Consequently, it has been proposed that circulating EVs may reflect the overall status of vascular health by integrating the endothelial, thrombotic, and inflammatory status in an individual 13,14,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMVs are small membrane vesicles (< 1.0 μm) released into the circulation in response to injury, activation, and apoptosis ( Dignat-George and Boulanger, 2011 ; Schiro et al, 2014 ), then, they have been used as a systemic marker of endothelial phenotype ( Lugo-Gavidia et al, 2021 ). Previous evidence has demonstrated an association of fat overload or DBF and increases in circulating EMV levels.…”
Section: Discussionmentioning
confidence: 99%
“…HTN is a complex and multifactorial illness attributed to both genetic and/or environmental factors involving persistent elevation of systemic blood pressure (BP) [ 2 ]. Despite a large degree of available therapeutic options, the prevalence of HTN is predicted to be increased over the next decade [ 3 ].…”
Section: Introductionmentioning
confidence: 99%